Pengalaman Ketergantungan Emosional Terhadap Pasangan pada Perempuan yang Mengalami Fatherless - Dhea Sintamaharani; Nadia Ariyani Hasanah Nuriyyatiningrum; Ikhrom Ikhrom (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The phenomenon of fatherlessness, where girls grow up without the physical or emotional presence of a father, has become a critical issue in adolescent psychosocial development. In Indonesia, rising divorce rates and family dysfunction have made this condition increasingly common. This study, conducted in Semarang, aims to explore the emotional experiences of women who have experienced fatherlessness, particularly in the context of romantic relationships. Using a qualitative approach with a phenomenological method, this research involved two female participants aged 19 and 21, selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings reveal complex emotional dynamics, including emotional dependency on partners, difficulty in building trust, and emotional instability within relationships. However, variations were found in how participants responded to fatherlessness: one showed strong emotional attachment to her partner, while the other exhibited emotional independence and distance. In conclusion, fatherlessness influences how women construct and engage in romantic relationships. This study recommends providing psychosocial support to young women from fatherless families to help them build healthy attachment and emotional regulation skills.